Effect of adding (Pow humus and potassium nitrate) on some chemical properties of ( Solanum lycopersicum L.) fruits in protected conditions in Najaf Governorate. - Aljebory, Razzak k.R.; Altalal, Ali M.M. (Journal of Kerbala for Agricultural Sciences, 2018)
An experiment was conducted on tomato plant cv. (Dombito hybrid ) during the season of 2016/2017 in unheated plastic houses at Al-Kufa Technical Institute, the Governorate of Najaf. Experiment was included 16 interacted treatments composed four treatmentas (0, 30, 60 and 90 g.m2) of Humat potassium granules (Pow humus)(T) as a source of humat in concentration of (85%) and four treatments (0, 20, 40 and 60 kg. Dunum) of potassium(A) via using potassium nitrate (KNO3) as a source of potassium in concentration (46.6%). Potassium nitrate and potassium Humat were added at four periods to study its effect on chemical properties of tomato plant fruits which included percentage of: TSS, vitamin C and total acidity percenatge of fruit for four pickings (3,6 ,9 and 12) The experiment was performed according to the Split-Plot-Design with three replicates, Means were compared according to Duncan's Multiple Range Test at the probability level of 0.05 Results showed that, the addition of potassium humat (T) and the addtion of potassium nitates (A) in all treatments were significantly increased in comparison with control treatment for all chemical characterstics of tamoto fruit and for all pickings. Results also cleared that interaction between (T) and (A) treatments were revealed a significant increas in (t4 a4) and (t4 a3) in comparsion with all treatments including the control treatment for all chemical characteristics and for all pickings, where the highest value was in the 12th picking of( 8.3 % and 28.9 mg.100 g.) of fruit for TSS and vitamin C. respectiviely, while control treatment for the same charcatreistcs gave the lowest value of 6.2 % and 11.7 mg.100 g. of fruit for TSS and vitamin C., respectiviely. Results of the total acidity percentage were significantly variable in all pickings and significantly increased in coparsion with the control treatment.